Decrypting Sri Lanka’s ‘black box’ amidst an Indo–China ‘great game’ - De Silva, Shakthi (Taylor & Francis, 2019)
Competition is a natural byproduct of major powers navigating an anarchic world. Small states operating in such a milieu however, face a dilemma when strategizing their foreign policy. At present, two regional behemoths – India and China – remain locked in a Realpolitik affray as they vie for influence by enticing and attracting South Asian states through economic, security and diplomatic initiatives. How do these structural dynamics impact Sri Lanka’s policymaking process? Moreover, has the island been able to mount a timely and appropriate response to structural dictates? In what way has domestic variables influenced and channeled policy preferences in Sri Lanka since 2015? By adopting a Neoclassical Realist frame of analysis, this paper appraises the impact made by the external environment and domestic intervening variables on the island’s foreign policy trajectory. It concludes that domestic intervening variables drew the island away from optimal choices in its relations with India and China.
Keywords: Sri Lanka; India; China; Foreign Policy